Antimicrobial Effects of Sansevieria Zeylanica Extracts on Urinary Tract Infection Associated Pathogens Isolated from Students Attending a Tertiary Institution (Journal of Basic and Applied Research in Biomedicine, 2023)
Urinary tract infections usually develop in the lower urinary tract and if not properly treated, they ascend to the upper urinary tract, causing severe damage to the kidneys. Sansevieria zeylenica is a plant known to be rich in phenolic compounds, which may be responsible for its antibacterial activities against Uropathogens.The study was aimed to investigate the antimicrobial effect of Sansevieria zeylenica extracts against isolate of UTI among students attending tertiary institution. A total of two hundred (200) urine samples were randomly collected from the students attending University of Benin into sterile universal containers and analyzed for the detection of Uropathogens using standard microbiological procedure while the leaf and root of Sansevieria zeylenica extraction was carried out with methanol using the Soxhlet apparatus.  The antimicrobial activity against the isolates was determined using Agar well diffusion and the minimum inhibitory concentration (MIC) of the extracts against the isolates was determined using the microdilution method. Of the 200 participants studied, 23 (11.5%) had growth of four bacteria species associated with urinary tract infection; Escherichia coli, Proteus vulgaris, Pseudomonas aeruginosa, and Staphylococcus aureus. The activity of both leaf and root extracts was greater at 200mg/ml against E. coli and P. vulgaris isolates, but at 400mg/ml against S. aureus with Minimum Inhibitory Concentrations of the leaf extract as 8mg/ml, 4mg/ml, 8mg/ml, and >16mg/ml against E. coli, S. aureus, P. vulgaris, and P. aeruginosa, respectively. The association of leaf extract and Ampicillin increases the activity of Ampicillin, producing a greater zone of inhibition (26mm) against P. vulgaris compared to Ampicillin alone (21mm) and leaf extract alone (16mm) giving rise to a synergistic effect. Sansevieria zeylanica extracts in this study can control Urinary Tract Infection and may be combined with conventional antibiotics as a treatment for Uropathogens. Though, further investigation would be requiring for the molecular mechanism behind its antibacterial activity.